Implementation of the Weighted Product Method in a Decision Support System for the Assessment of Medical Personnel at Tais Regional General Hospital - Julianda, Figora; Jumadi , Juju; Fredricka, Jhoanne (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Medical performance assessment aims to improve service quality. The obstacle faced is the difficulty of evaluating medical performance objectively due to the many criteria and responsibilities of medical personnel for services. To overcome these obstacles, a Decision Support System using the Weight Product method is needed to be utilized as a tool in supporting the decision-making process. The Weight Product method uses multiplication to connect attribute ratings, where the rating of each attribute is first multiplied by the weight of the attribute concerned. The system implementation uses Visual Basic 2010 programming language and the method used in this research is the waterfall method. From the test results, it can be concluded that the medical performance assessment using Weight Product can be done well by taking the top number of medical personnel from the ranking process.